A high-strength, low-shrinkage dental restoration resin and preparation method thereof

By using silanized inorganic fillers, resin monomers and photoinitiators in dental repair resins, combining free radicals and cationic polymerization, the intensity and shrinkage rate of the resin is regulated, and the volume shrinkage problem of dental repair resins during polymerization is solved, and the volume shrinkage problem of dental repair resins is achieved. The effect of high strength and low shrinkage improves the stability and clinical application of the material.

CN116942540BActive Publication Date: 2024-12-13LONGLY BIOTECH WUHAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310984897.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2024-12-13
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

The volume shrinkage effect generated by dental restoration resin during polymerization limits the development of dental restoration resin materials, resulting in material breakage, edge micro leakage and adverse consequences after surgery. How to overcome volume shrinkage during polymerization is a hot topic and difficulty in research.

Method used

Using silanized inorganic fillers, resin monomers and photoinitiators, the strength and polymerization shrinkage of the resin are adjusted by combining radical polymerization and cationic polymerization. The specific ratio is 60% to 80% of silanized inorganic fillers, and the resin monomer 19 % to 36%, photoinitiator 1 to 4%, wherein the main resin monomer includes Bis-EAR and SynaEpoxy S-100, the expansion monomer is BMSOC, the resin diluent monomer is GMA, and the components interact to reduce Volume shrinkage.

Benefits of technology

A dental repair resin with high strength and low shrinkage has been achieved, with a bending strength range of 88.68~126.54MPa, and the polymerization shrinkage rate has been significantly reduced to 1.81%, which has improved the service life of the material and clinical application effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116942540B_ABST
    Figure CN116942540B_ABST
Patent Text Reader

Abstract

The present invention provides a high-strength and low-shrinkage dental restoration resin and a preparation method thereof, comprising 60% to 80% of silanized inorganic filler, 19% to 36% of resin monomer and 1% to 4% of photoinitiator; wherein the resin monomer comprises a resin main monomer, an expansion monomer and a resin diluent monomer. The preparation method of the dental restoration resin is simple, wherein the silanized inorganic filler, the main monomer component and the expansion monomer component in the resin monomer can be simultaneously subjected to free radical polymerization and cationic polymerization, and the components interact with each other and are indispensable, and the volume shrinkage rate of the monomer during the polymerization process can be significantly reduced while the resin strength is enhanced. The bending strength of the obtained dental restoration resin ranges from 88.68 to 126.54 MPa, and the highest can reach 126.54 MPa, and the polymerization shrinkage rate is significantly reduced, and the lowest can reach 1.81%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of dental restoration materials, and in particular to a high-strength and low-shrinkage dental restoration resin and a preparation method thereof. Background Art

[0002] Since RL Bowen synthesized bisphenol A-glycidyl methacrylate (Bis-GMA), dental resins have attracted widespread attention as dental restoration materials due to their good physical and chemical properties, biocompatibility, and simple and convenient operation. Compared with Bis-GMA, bisphenol A epoxy acrylate (Bis-EAR), as a larger molecular weight oligomer, has a lower polymerization shrinkage rate and is a good substitute for Bis-GMA in low shrinkage resin systems. Dental resins are composed of resin monomers, inorganic fillers, and photoinitiators. Resin monomers are divided into resin main monomers and resin diluent monomers, and photoinitiators are divided into main initiators and co-initiators. Although scientific researchers have conducted in-depth research in the field of light-cured dental restoration resin materials, the volume shrinkage effect of the resin during the polymerization process still greatly limits the development of dental restoration resin materials.

[0003] During the polymerization process of resin monomers, double bonds are opened, and the transformation of intermolecular van der Waals bonds to covalent bonds reduces the distance between molecules, which eventually leads to the occurrence of macroscopic volume shrinkage. The polymerization shrinkage rate is proportional to the total content of resin monomers. As the total content of monomers increases, shrinkage occurs between interfaces. The volume shrinkage effect during the light curing of resins leads to the internal resin and resin-tooth tissue forces, forming marginal micro-leakage. Substances such as food, bacteria and toxins will enter the leakage gap, leading to adverse consequences such as postoperative allergies, marginal staining and secondary caries, which ultimately affect the service life and clinical application effect of dental restoration resins. How to overcome the volume shrinkage during the polymerization process is a hot and difficult problem in the research of dental restoration resin materials.

[0004] Expandable monomers are monomer molecules that can expand in volume during the polymerization process. By adding expandable monomers to the polymerization system, the volume shrinkage effect produced during free radical polymerization and cationic polymerization can be partially offset. It has been successfully used in the polymerization modification of epoxy resins. The expandable monomer 3,9-dimethyl-1,5,7,11-tetraoxospiro[5,5]undecane (BMSOC) contains both double bond functional groups that can be free radical polymerized and epoxy functional groups that can be cationic polymerized. It can undergo free radical polymerization and cationic polymerization at the same time, thereby synergistically regulating the strength and polymerization shrinkage of dental restoration resin materials. However, the resin material formed by BMSOC may have defects such as low strength or large shrinkage effect due to the aggregation of some unreacted monomers.

[0005] Therefore, whether it is possible to prepare a dental restorative material with high strength and small volume shrinkage effect is an urgent problem to be solved in the art. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to prepare a dental restorative material with high strength and low shrinkage by using silanized inorganic fillers, resin monomers and photoinitiators, so as to provide a strategy for solving the problems of material fracture and polymerization shrinkage of dental restorative resins during service.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a high-strength, low-shrinkage dental restoration resin, wherein the raw materials of the dental restoration resin, measured by mass percentage, include:

[0009] Silanized inorganic filler 60% to 80%;

[0010] Resin monomer 19% to 36%;

[0011] Photoinitiator 1% to 4%;

[0012] Wherein, the resin monomers include resin main monomers, expansion monomers and resin diluent monomers.

[0013] In the present invention, the silanized inorganic filler and the main monomer component and the expansion monomer component in the resin monomer can be simultaneously subjected to free radical polymerization and cationic polymerization, and the resin strength and polymerization shrinkage can be coordinated and regulated while ensuring the polymerization rate.

[0014] In the present invention, the mass percentage of the silanized inorganic filler is 60% to 80%, for example, it can be 60%, 62%, 65%, 68%, 70%, 72%, 74%, 75%, 76%, 78% or 80%;

[0015] The mass percentage of the resin monomer is 19% to 36%, for example, it can be 19%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34% or 36%, etc.;

[0016] The mass percentage of the photoinitiator is 1% to 4%, for example, it can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.4%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8% or 4%.

[0017] As a preferred technical solution of the present invention, the main monomer of the resin includes bisphenol A epoxy acrylate (Bis-EAR) and 3,4-epoxycyclohexyl methyl methacrylate (SynaEpoxyS-100).

[0018] In the present invention, when selecting the main monomer of the resin, both Bis-EAR and Bis-GMA (bisphenol A-glycidyl methacrylate) can be used as the main monomer of the resin. However, in the actual preparation process, the inventors found that the use of Bis-EAR in this system has a better effect. This better effect is due to the lower polymerization shrinkage of Bis-EAR itself on the one hand; on the other hand, compared with Bis-GMA, the richer rigid structure in the main chain of the Bis-EAR molecule makes its strength more excellent.

[0019] Preferably, the swelling monomer is 3,9-dimethylene-1,5,7,11-tetraoxaspiro[5,5]undecane (BMSOC).

[0020] Preferably, the resin diluent monomer is glycidyl methacrylate (GMA).

[0021] In the present invention, the Bis-EAR, SynaEpoxy S-100, BMSOC and GMA are used as main monomers of the resin, and the molecules cooperate with each other. Specifically, the main monomers of the resin (i.e., Bis-EAR and SynaEpoxy S-100) and the resin diluent monomer (GMA) both contain cationically polymerizable epoxy functional groups and free radically polymerizable double bond functional groups; the expansion monomer (BMSOC) contains more abundant cationically polymerizable epoxy functional groups.

[0022] At the same time, the double bond functional groups in the main resin monomer, resin diluent monomer and silanized inorganic filler can undergo free radical polymerization; the epoxy functional groups in the main resin monomer, resin diluent monomer, expansion monomer and silanized inorganic filler can undergo cationic polymerization, which can reduce the volume shrinkage effect during the free radical polymerization process. In addition, cationic polymerization is not affected by oxygen inhibition, and the reaction can still proceed after the light stops, which is conducive to improving the strength.

[0023] Preferably, the mass of the expansion monomer in the present invention is 10% to 20% of the total mass of the main resin monomer, for example, it can be 10%, 12%, 14%, 15%, 16%, 18%, 19% or 20%.

[0024] Preferably, the resin diluent monomer accounts for 10% to 20% of the total mass of the resin main monomer, for example, it may be 10%, 12%, 14%, 15%, 16%, 18%, 19% or 20%.

[0025] As a preferred technical solution of the present invention, the ratio of the resin main monomer, the expansion monomer and the resin diluent monomer is 1:(0.1-0.2):(0.1-0.2), preferably 1:(0.13-0.2):(0.1-0.13), and more preferably 1:0.2:0.1.

[0026] The resin main monomer, expansion monomer and resin diluent monomer described in the present invention are mixed in a ratio of 1:(0.1-0.2):(0.1-0.2), for example, it can be 1:0.1:0.1, 1:0.1:0.15, 1:0.15:0.15, 1:0.1:0.2, 1:0.15:0.1, 1:0.2:0.1, 1:0.18:0.12 or 1:0.12:0.18, etc.

[0027] As a preferred technical solution of the present invention, the mass ratio of bisphenol A epoxy acrylate to 3,4-epoxycyclohexylmethyl methacrylate is 1:(0.2-1.2), for example, it can be 1:0.2, 1:0.4, 1:0.5, 1:0.6, 1:0.8 or 1:1.2.

[0028] Preferably, the mass of the resin diluent monomer is 20-40% of the mass of bisphenol A epoxy acrylate, for example, it can be 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38% or 40%, etc.

[0029] As a preferred technical solution of the present invention, the silanized inorganic filler is a mixture of micron silicon dioxide and nano silicon dioxide.

[0030] Preferably, the surface modification agent of the silanized inorganic filler is γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane.

[0031] Preferably, the mass ratio of γ-glycidyloxypropyltrimethoxysilane to vinyltriethoxysilane is 1:(0.5-2), for example, it can be 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8 or 1:2, etc.

[0032] In the present invention, the preparation method of the silanized inorganic filler can adopt the following steps:

[0033] A mixed solution containing ethanol, ammonium hydroxide and deionized water is prepared, and ethyl orthosilicate is added, stirred for reaction, cooled to room temperature and centrifuged for drying, the obtained product is dispersed in cyclohexane, and propylamine, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane are added, stirred for reaction; cooled to room temperature and centrifuged for drying to obtain a silanized inorganic filler.

[0034] As a preferred technical solution of the present invention, the photoinitiator is a ternary initiator system; the ternary initiator system comprises camphorquinone (CQ), diphenyliodonium hexafluorophosphate (PI) and dimethylaminoethyl methacrylate (DMAEMA).

[0035] In the present invention, the ternary photoinitiator system (CQ / PI / DMAEMA) initiates the free radical / cationic copolymerization reaction of the uncured composite resin paste and cures it.

[0036] Preferably, the CQ, PI and DMAEMA form a ternary initiator system in a mass ratio of 1:(1-3):(1-2), for example, 1:1:1, 1:1:1.5, 1:1:2, 1:1.5:1.5, 1:1.5:2, 1:2:2, 1:2.5:2, 1:3:2, etc., preferably 1:3:2.

[0037] As a preferred technical solution of the present invention, the raw materials of the dental restoration resin, measured by mass percentage, also include:

[0038] Silanized inorganic filler 60% to 70%;

[0039] Resin monomer 29% to 38%;

[0040] Photoinitiator 1%~2%.

[0041] In a second aspect, the present invention provides a method for preparing the high-strength and low-shrinkage dental restorative resin as described in the first aspect, comprising the following steps:

[0042] The silanized inorganic filler, the resin monomer and the photoinitiator are premixed under light-proof conditions, and then placed in a three-roll mill for further mixing;

[0043] After vacuum negative pressure treatment, an uncured composite resin paste is obtained;

[0044] After light curing, the high-strength and low-shrinkage dental restoration resin is obtained.

[0045] In a third aspect, the present invention further provides a use of the high-strength, low-shrinkage dental restoration resin as described in the first aspect in the preparation of a dental restoration material.

[0046] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The high-strength, low-shrinkage dental restoration resin provided by the present invention comprises a main monomer component, an expansion monomer and a resin diluent monomer in the resin monomer. The main resin monomer includes Bis-EAR and SynaEpoxy S-100, the expansion monomer is BMSOC, and the resin diluent monomer is GMA; the four components constitute the resin monomer in a certain proportion. The modified filler component and the main monomer component and the expansion monomer component in the resin monomer can all be subjected to free radical polymerization and cationic polymerization at the same time. The components interact with each other and are indispensable. The resin strength and polymerization shrinkage rate can be synergistically regulated while ensuring the polymerization rate.

[0049] The bending strength of the dental restoration resin of the present invention ranges from 88.68 to 126.54 MPa, and can reach 126.54 MPa at the highest. The polymerization shrinkage rate is significantly reduced, and can reach 1.81% at the lowest. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The figure is a bar graph showing the bending strength of the corresponding resins in the embodiments of the present invention and the control examples.

[0051] Figure 2 It is a histogram of polymerization shrinkage of the corresponding resins of the embodiments of the present invention and the control examples. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0053] In the following examples, unless otherwise specified, all reagents and consumables used were purchased from conventional reagent manufacturers in the field; unless otherwise specified, all experimental methods and technical means used were conventional methods and means in the field.

[0054] In the present invention, the silanized inorganic filler is prepared by the following method:

[0055] Prepare a mixed solution containing 600 mL of ethanol, 400 mL of ammonium hydroxide and 100 mL of deionized water, add 60 mL of ethyl orthosilicate, and stir at 60°C for 2 h;

[0056] After cooling to room temperature, the mixture was centrifuged and dried. The obtained product was dispersed in 140 mL of cyclohexane, and 0.14 mL of propylamine, 0.83 mL of γ-glycidyloxypropyltrimethoxysilane and 0.88 mL of vinyltriethoxysilane were added. The mixture was stirred and reacted at 60 °C for 2 h.

[0057] The mixture was cooled to room temperature and centrifuged and dried to obtain the silanized inorganic filler.

[0058] Example 1

[0059] This embodiment provides a dental restoration resin, and the specific preparation method is as follows:

[0060] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0061] The mass percentages of the silanized inorganic filler, the resin monomer and the photoinitiator are 60%, 38.4% and 1.6% respectively.

[0062] The resin monomers include Bis-EAR, Syna Epoxy S-100, BMSOC and GMA, and their mass fractions account for 16%, 16%, 3.2% and 3.2% of the total raw material amount respectively (38.4% in total).

[0063] The photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2.

[0064] The above materials are put into a three-roll mill according to the proportions for further mixing, and subjected to vacuum negative pressure treatment to obtain an uncured composite resin paste;

[0065] Under light irradiation in the wavelength range of 430-490nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0066] Example 2

[0067] This embodiment provides a dental restoration resin, and the specific preparation method is as follows:

[0068] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0069] The mass percentages of the silanized inorganic filler, the resin monomer and the photoinitiator are 62%, 36.4% and 1.6% respectively.

[0070] The resin monomers include Bis-EAR, Syna Epoxy S-100, BMSOC and GMA, and their mass fractions account for 14%, 14%, 5.6% and 2.8% of the total raw material amount respectively (36.4% in total).

[0071] The photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2.

[0072] Finally, under the irradiation of light in the wavelength range of 430-490nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0073] Example 3

[0074] This embodiment provides a dental restoration resin, and the specific preparation method is as follows:

[0075] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0076] The mass percentages of the silanized inorganic filler, the resin monomer and the photoinitiator are 64.8%, 33.6% and 1.6% respectively.

[0077] The resin monomers include Bis-EAR, Syna Epoxy S-100, BMSOC and GMA, and their mass fractions account for 16%, 16%, 3.2% and 3.2% of the total raw material amount respectively (33.6% in total).

[0078] The photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2.

[0079] Finally, under light irradiation in the wavelength range of 430 to 490 nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0080] Example 4

[0081] This embodiment provides a dental restoration resin, and the specific preparation method is as follows:

[0082] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0083] The mass percentages of the silanized inorganic filler, the resin monomer and the photoinitiator are 68%, 30.4% and 1.6% respectively.

[0084] The resin monomers include Bis-EAR, Syna Epoxy S-100, BMSOC and GMA, and their mass fractions account for 16%, 8%, 3.2% and 3.2% of the total raw material amount respectively (30.4% in total).

[0085] The photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2.

[0086] Under light irradiation in the wavelength range of 430-490nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0087] Example 5

[0088] This embodiment provides a dental restoration resin, and the specific preparation method is as follows:

[0089] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0090] The mass percentages of the silanized inorganic filler, the resin monomer and the photoinitiator are 68%, 30.4% and 1.6% respectively.

[0091] The resin monomers include Bis-EAR, Syna Epoxy S-100, BMSOC and GMA, and their mass fractions account for 8%, 16%, 3.2% and 3.2% of the total raw material amount respectively (30.4% in total).

[0092] The photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2.

[0093] Under light irradiation in the wavelength range of 430-490nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0094] Comparative Example 1

[0095] This comparative example provides a dental restoration resin, and the specific preparation method is as follows:

[0096] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0097] In this scheme, the expandable monomer BMSOC is not added; wherein the mass fractions of the silanized inorganic filler, Bis-EAR, SynaEpoxyS-100 and GMA are 69.6%, 12%, 12% and 4.8% respectively, and the mass fraction of the photoinitiator is 1.6%, and they are further mixed in a three-roll mill and subjected to vacuum negative pressure treatment to obtain an uncured composite resin paste; the photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2;

[0098] Finally, under light irradiation in the wavelength range of 430-490nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0099] Comparative Example 2

[0100] This comparative example provides a dental restoration resin, and the specific preparation method is as follows:

[0101] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0102] In this scheme, Bis-EAR is not added, wherein the mass fractions of silanized inorganic filler, SynaEpoxyS-100, BMSOC and GMA are 64.8%, 24%, 4.8%, 4.8% respectively, and the mass fraction of photoinitiator is 1.6%, and further mixed in a three-roll mill, and treated with vacuum negative pressure to obtain an uncured composite resin paste; the photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2;

[0103] Finally, under light irradiation in the wavelength range of 430 to 490 nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0104] Comparative Example 3

[0105] This comparative example provides a dental restoration resin, and the specific preparation method is as follows:

[0106] Premixing γ-glycidyloxypropyltrimethoxysilane with a silanized inorganic filler modified with vinyltriethoxysilane, a resin monomer and a photoinitiator under light-proof conditions;

[0107] In this scheme, SynaEpoxyS-100 is not added, wherein the mass fractions of silanized inorganic filler, Bis-EAR, BMSOC and GMA are 64.8%, 24%, 4.8% and 4.8% respectively, and the mass fraction of photoinitiator is 1.6%, and further mixed in a three-roll mill, and subjected to vacuum negative pressure treatment to obtain an uncured composite resin paste; the photoinitiator is a ternary photoinitiator system (CQ / PI / DMAEMA), wherein the ratio of CQ / PI / DMAEMA is 1:3:2;

[0108] Finally, under light irradiation in the wavelength range of 430 to 490 nm, a free radical / cationic copolymerization reaction occurs through a ternary photoinitiator system and solidifies to obtain a dental restorative resin.

[0109] Comparative Example 4

[0110] This comparative example provides a dental restorative resin, in which the silanized inorganic filler is modified only with γ-glycidyloxypropyltrimethoxysilane, and the specific preparation method is as follows:

[0111] (1) Preparation of silanized inorganic filler

[0112] Prepare a mixed solution containing 600 mL of ethanol, 400 mL of ammonium hydroxide and 100 mL of deionized water, add 60 mL of ethyl orthosilicate, and stir at 60°C for 2 h;

[0113] After cooling to room temperature, the mixture was centrifuged and dried. The obtained product was dispersed in 140 mL of cyclohexane, and 0.14 mL of propylamine and 1.71 mL of γ-glycidyloxypropyltrimethoxysilane were added. The mixture was stirred and reacted at 60 °C for 2 h.

[0114] After cooling to room temperature, the mixture was centrifugally dried to obtain a silanized inorganic filler modified with only γ-glycidyloxypropyltrimethoxysilane.

[0115] (2) premixing the silanized inorganic filler modified with γ-glycidyloxypropyltrimethoxysilane, the resin monomer and the photoinitiator under light-proof conditions;

[0116] The remaining steps and components remain the same as in Example 2.

[0117] Comparative Example 5

[0118] This comparative example provides a dental restorative resin, which differs from Example 2 only in that Bis-EAR is replaced with Bis-GMA;

[0119] The remaining steps and components are consistent with those in Example 2.

[0120] Comparative Example 6

[0121] This control example provides a dental restorative resin, which differs from Example 2 only in that it does not contain the diluent monomer GMA; in this scheme, the mass fractions of silanized inorganic filler, Bis-EAR, and BMSOC are 64.8%, 14%, 14%, and 5.6%, respectively; the remaining steps are consistent with Example 2.

[0122] In the preparation of the reagent of Reference Example 6, since the diluent monomer GMA was not added, the viscosity of the uncured resin obtained during the preparation process was relatively high, and the normal steps (i.e., the same steps as Example 2) could not be used for preparation, and specific equipment was required to complete the steps. Since the preparation was too difficult, it did not meet the actual production requirements. Therefore, the dental restoration resin corresponding to Reference Example 6 was not prepared in the present invention.

[0123] The raw materials of the dental restoration resin prepared in the present invention are shown in Table 1;

[0124] Table 1

[0125]

[0126]

[0127] Characterization of dental restorative resins

[0128] Referring to the international standard "ISO4049-2009", the flexural strength of the low shrinkage and high strength dental restoration resin was tested using a universal testing machine (E44.104, USA); referring to "ISO4216:2021", the polymerization shrinkage rate of the low shrinkage and high strength dental restoration resin was tested and calculated.

[0129] The bending strength and polymerization shrinkage of the dental restoration resins prepared in Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 2 below;

[0130] Table 2

[0131] plan Bending strength(MPa) Polymerization shrinkage (%) Example 1 88.68±6.28 3.26±0.34 Example 2 126.54±7.71 1.81±0.21 Example 3 104.34±6.54 2.80±0.48 Example 4 122.54±5.23 1.97±0.46 Example 5 107.81±2.45 2.24±0.51 Comparative Example 1 92.41±4.89 8.41±0.92 Comparative Example 2 62.26±8.82 2.42±0.22 Comparative Example 3 96.47±6.14 4.79±0.18 Comparative Example 4 74.28±4.72 2.16±0.26 Comparative Example 5 112.92±6.12 2.88±0.47

[0132] The bending strength of the corresponding resins of Examples 1 to 5 of the present invention and Comparative Examples 1 to 5 is as follows: Figure 1 shown.

[0133] The polymerization shrinkage of the corresponding resins in Examples 1 to 5 of the present invention and Comparative Examples 1 to 5 is as follows: Figure 2 shown.

[0134] From Table 2 and Figure 1 and Figure 2 It can be seen that the dental restoration resin prepared in the embodiments provided in the present invention has a bending strength of 88.68 to 126.54 MPa and a polymerization shrinkage of 1.81% to 3.26%. The components and the ratios between the components selected in Embodiment 2 are the best, and the bending strength can reach 126.54 MPa, and the polymerization shrinkage is only 1.81%.

[0135] Combining Example 2 with Comparative Examples 1 to 3 and Comparative Example 6, it can be seen that the main monomer of the resin, the expansion monomer and the resin diluent monomer are indispensable in the present invention. The absence of any one of the components will lead to a decrease in the performance of the obtained dental restoration resin.

[0136] Combining Example 2 with Example 1, it can be seen that in this application, when the ratio of the main resin monomer, the expansion monomer and the resin diluent monomer is 1:0.1:0.1 respectively, the effect is worse than the ratio of 1:0.2:0.1; and the performance of Example 1 is worse than that of Examples 3 to 4 and Control Example 5, and even the bending strength is lower than that of Control Example 1 and Control Example 3, indicating that the ratio of the main resin monomer, the expansion monomer and the resin diluent monomer is more important. Only by selecting a suitable ratio can the bending strength and polymerization shrinkage performance be better. The ratio of the three in the present invention is preferably 1:(0.13~0.2):(0.1~0.13), and more preferably 1:0.2:0.1.

[0137] Combining Example 2 with Comparative Examples 4 and 5, it can be seen that if the inorganic filler does not use a double modifier or replaces Bis-EAR with Bis-GMA, its performance is significantly lower than that of Example 2. And for Example 2 and Comparative Example 5, in addition to the lower polymerization shrinkage of Bis-EAR itself, in the system of the present invention, Bis-EAR also obtains higher bending strength than Bis-GMA, which is quite unexpected. The inventors preliminarily analyzed that it is due to the rigid structure on Bis-EAR, which further improves the bending strength of the material. In summary, the dental restoration resin provided by the present invention has the characteristics of high strength and low shrinkage, and can solve the problems of material breakage and polymerization shrinkage of dental restoration resins during service.

[0138] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high-strength, low-shrinkage dental restorative resin, characterized in that: The raw materials of the dental restoration resin include, by weight percentage: Silanized inorganic filler 60% to 80%; Resin monomer 19% to 36%; Photoinitiator 1% to 4%; Wherein, the silanized inorganic filler is a mixture of micron silicon dioxide and nano silicon dioxide, and the surface modification agent of the silanized inorganic filler is γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane; The silanized inorganic filler is prepared by the following method: A mixed solution containing ethanol, ammonium hydroxide and deionized water is prepared, ethyl orthosilicate is added, stirred for reaction, cooled to room temperature and then centrifuged for drying, the obtained product is dispersed in cyclohexane, propylamine, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane are added, stirred for reaction, cooled to room temperature and then centrifuged for drying to obtain a silanized inorganic filler; The resin monomers include a resin main monomer, an expansion monomer and a resin diluent monomer; The resin main monomer includes bisphenol A epoxy acrylate and 3,4-epoxycyclohexyl methyl methacrylate, the expansion monomer is 3,9-dimethylene-1,5,7,11-tetraoxospiro[5,5]undecane, and the resin diluent monomer is glycidyl methacrylate.

2. The high-strength, low-shrinkage dental restorative resin according to claim 1, characterized in that: The ratio of the resin main monomer, the expansion monomer and the resin diluent monomer is 1:(0.1-0.2):(0.1-0.2).

3. The high-strength, low-shrinkage dental restorative resin according to claim 1, characterized in that: The mass ratio of bisphenol A epoxy acrylate to 3,4-epoxycyclohexyl methyl methacrylate in the main monomer of the resin is 1:(0.2-1.2); The mass of the resin diluent monomer is 20% to 40% of the mass of bisphenol A epoxy acrylate.

4. The high-strength, low-shrinkage dental restorative resin according to claim 1, characterized in that: The mass ratio of the γ-glycidyloxypropyltrimethoxysilane to vinyltriethoxysilane is 1:(0.5-2).

5. The high-strength, low-shrinkage dental restorative resin according to claim 1, characterized in that: The photoinitiator is a ternary initiator system.

6. The high-strength, low-shrinkage dental restorative resin according to claim 5, characterized in that: The photoinitiator comprises camphorquinone, diphenyliodonium hexafluorophosphate and dimethylaminoethyl methacrylate; The camphorquinone, diphenyliodonium hexafluorophosphate and dimethylaminoethyl methacrylate form a ternary initiation system in a mass ratio of 1:(1-3):(1-2).

7. A method for preparing a high-strength, low-shrinkage dental restorative resin according to any one of claims 1 to 6, characterized in that: The steps include: The silanized inorganic filler, the resin monomer and the photoinitiator are premixed under light-proof conditions, and then placed in a three-roll mill for further mixing; After vacuum negative pressure treatment, an uncured composite resin paste is obtained; After light curing, the high-strength and low-shrinkage dental restoration resin is obtained; The silanized inorganic filler is modified using γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane, and the modification steps include: A mixed solution containing ethanol, ammonium hydroxide and deionized water is prepared, ethyl orthosilicate is added, the mixture is stirred for reaction, and the mixture is cooled to room temperature and then centrifuged for drying; The obtained product is then dispersed in cyclohexane, and propylamine, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane are added, and stirred for reaction; The mixture was cooled to room temperature and centrifuged and dried to obtain the silanized inorganic filler.

8. Use of the high-strength, low-shrinkage dental restorative resin according to any one of claims 1 to 6 in the preparation of dental restorative materials.

Citation Information

Patent Citations

  • Preparation method capable of realizing chemical blending of modified nano silicon dioxide particles in acrylate monomer

    CN102911530A

  • Low-shrinkage dental composite resin and its preparation method

    CN111557855B

  • A method of making dental articles

    CN113905688A